Midcingulate involvement in progressive supranuclear palsy and tau positive frontotemporal dementia. Issue 9 (25th June 2012) - Chiu, Wang Zheng; Papma, Janne M; de Koning, Inge; Donker Kaat, Laura; Seelaar, Harro; Reijs, Ambroos E M; Valkema, Roelf; Hasan, Djo; Boon, Agnita J W; van Swieten, John Cornelis
Abstract : Background: Progressive supranuclear palsy (PSP) patients often exhibit cognitive decline and behavioural changes during the disease course. In a subset, these symptoms may be the presenting manifestation and can be similar to those in frontotemporal dementia (FTD). However, correlation studies between quantitative imaging measures and detailed neuropsychological assessment are scarce. The aim of this study was to investigate the functional role of affected brain regions in cognition in PSP compared with controls and subsequently examine these regions in FTD patients with known tau pathology (FTD tau). Methods: 21 PSP patients, 27 healthy controls and 11 FTD tau patients were enrolled. All participants underwent neuropsychological testing and technetium-99m-hexamethyl-propylenamine-oxime single photon emission CT. Regression slope analyses were performed in statistical parametric mapping to find significant associations between neuropsychological test results and brain perfusion. Results: PSP patients showed hypoperfusion in the midcingulate cortex (MCC) of which the posterior part correlated with Stroop III and Weigl. In FTD tau patients, MCC involvement was located more anterior and correlated with Stroop III and Wisconsin Card Sorting Test concepts. The degree of hypoperfusion in the anterior cortex and MCC in the disorders differed in the subgenual anterior cingulate cortex only. Conclusions: The posterior part of the MCC is prominently involved in the neurodegenerative process of PSP, and the severity of its hypoperfusion correlated with the extent of executive dysfunction. In FTD tau, this cognitive domain was associated with anterior MCC involvement. The degree of hypoperfusion in these regions did not differ between PSP and FTD tau. These observations provide insight into the role of the cingulate cortex in cognitive dysfunction in these neurodegenerative disorders and warrant further investigations.